Legal Reconstruction of the Use of Checks as Security Instruments in Banking Credit Agreements in Indonesia - Kharisma Jomenta Surbakti; Evita Isretno Israhadi (International Journal of Social Service and Research, 2026)
A credit agreement constitutes the legal basis of the relationship between a bank as creditor and a customer as debtor in banking activities. In practice, credit agreements often include additional clauses requiring the debtor to provide checks as a form of payment guarantee. However, the use of checks as security instruments is not explicitly regulated under Indonesian law, which creates legal uncertainty, particularly when a check cannot be honored due to insufficient funds. This research aims to analyze (i) the legal framework governing the use of checks as security in credit agreements, (ii) the legal position of checks within the perspective of civil law and banking law, and (iii) the boundary between civil default and criminal liability. Furthermore, this study proposes a legal reconstruction to ensure fairness and legal certainty in banking practices. This research uses a normative juridical method with statutory and conceptual approaches. The analysis refers to the Indonesian Civil Code, particularly Article 1320 and Article 1338, the Commercial Code provisions on checks, and relevant banking regulations. The results indicate that checks function only as additional guarantees and do not provide proprietary rights or preferential rights to creditors. The failure of a check to be honored should primarily be treated as a civil default. Criminal liability may only arise if there is evidence of fraudulent intent at the time the check is issued. Therefore, a legal reconstruction is necessary to prevent the misuse of criminal law in civil disputes and to provide clearer regulatory guidelines.